Analyzing the Performance of IC Engine using LabView - Ramasamy., R (International Journal of Psychosocial Rehabilitation, 2017)
With a growing demand for transportation IC engines have gained lot of importance in automobile industry. It is therefore necessary to produce efficient and economical engines. While developing an IC engine it is required to take in consideration all the parameters affecting the engines design and performance. There are enormous parameters so it becomes difficult to account them while designing an engine. So it becomes necessary to conduct tests on the engine and determine the measures to be taken to improve the engines performance. Engine performance is an indication of the degree of success of the engine performs its assigned task, i.e. the conversion of the chemical energy contained in the fuel into the useful mechanical work. Performance of an IC Engine depends on it some of the performance parameters like inlet temperature, exhaust gas temperature, air fuel ratio etc. These parameters are measured by different methods and conditions.